Silcrete as a valuable resource for stone tool manufacture and its use by Paleo-American hunter–gatherers in southeastern South America - Nami, Hugo Gabriel (2017)
In the mid-eastern part of the southern cone of South America, sources of silcrete extend from eastern Entre Ríos province in Argentina to mid-western Uruguay. As a material for stone tool manufacture this rock was used with different levels of intensity in the regional archaeological record. In areas currently covered by Buenos Aires province in Argentina and the Republic of Uruguay in particular, diverse Paleo-American artifacts were made with this material between ~ 13 and 12 cal. ka BP. Due to this material's exploitation by early human occupiers, this paper addresses and discusses its distribution, source location, quality, use, and its probable preference by one of the earliest groups of foragers living during the late Pleistocene.